Parents’ and children’s experiences of participating in a randomized controlled clinical trial: AIDIT-QS - Peter Sand; Emelie Kinberg; Frida Sundberg; Gun Forsander (International Journal of Qualitative Studies on Health & Well-Being)
Participation in a paediatric, complex randomized controlled trial (RCT) might add to the family burden when a child is diagnosed with a severe disease. Although important, there are only a limited number of papers describing this aspect of research from the family point of view. This study explored parents’ and children’s experiences of participation in a research study shortly after the child had been diagnosed with type 1 diabetes. Sixteen parents (nine mothers, seven fathers) and nine children were interviewed by an independent researcher about their inducement, the decision-making process within the family which led to their participation, and their experience of having done so. The result showed that the parents wanted to contribute to improve treatment for children with diabetes in general but also specifically for their own child. Older children were more involved in the decision making than the younger children. Study information needs to be communicated clearly and effectively since decision-making based on information of a clinical trial directly after the child’s diabetes onset proved difficult. Being randomized to the intervention group in this specific study was considered somewhat burdensome. However, parental participants in both intervention and control group claimed that they would recommend participation in research studies to other parents in a similar situation, and so did the children. There was no difference between the mothers’ and fathers’ experiences.